Implementation design for assembly in two-wheel motorcycle chassis design (case study at hummeroad workshop) - Debby Octavianto; Ribangun Bamban Jakaria (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
The use of two-wheeled motorcycles is quickly increasing in Indonesia. This is because two-wheeled motorcycles are a versatile, economical, and simple mode of transportation for daily purposes. Aside from being a mode of transportation, two-wheeled motorcycles are also utilised to transmit art through modification. The chassis of a two-wheeled motorcycle is one of the components that can be adjusted. The chassis is a frame composed of iron or steel that supports the vehicle's weight and load, including the engine and occupants. Chassis changes at the Hummerroad repair business are done on a made-to-order basis. As a result, before making chassis alterations, it is vital to identify the desired assembly design and estimate the expenses involved. This study attempts to: (1) learn about the implementation of Design for Assembly (DFA) on two-wheeled motorcycle chassis at the Hummerroad Workshop. (2) Determine the effect of the DFA approach on the assembly costs of two-wheeled motorcycle chassis at the Hummerroad Workshop; (3) Determine the effect of the DFA method on the design efficiency of two-wheeled motorcycle chassis at the Hummerroad Workshop. This study employs DFA to create a customised two-wheeled motorcycle chassis. The study's findings suggest that labour costs are reduced by IDR 200,000, materials are reduced by IDR 500,000, assembly time is reduced by up to 1.39 hours, and assembly efficiency is increased to 14% per item. This demonstrates that the DFA method can serve as an option for product design and development.